CROATIA AND THE STRATEGY OF (EXTENDED) DETERRENCE IN THE CONTEXT OF THE UKRAINE CONFLICT: NORMATIVE FOUNDATIONS AND PRACTICAL CHALLENGES - Pop-Lazić, Isidora (National interest, 2025)
This paper examines Croatia's involvement in (extended) deterrence strategy as a critical component of NATO's collective defense strategy and its broader implications for regional stability, particularly in bilateral relations with Serbia. The research aims to analyze how Croatia’s NATO membership has influenced its strategic positioning and contributed to the development of its security policies. It also explores the impact of the Ukraine conflict on NATO’s strategic priorities and Croatia’s alignment with these objectives. The research draws on a comparative analysis of Croatia's national security and defense strategies from 2002 to 2017, reflecting a transition shaped by NATO and EU integration. The study demonstrates how Croatia has integrated its national defense strategy with broader Euro-Atlantic frameworks. Special attention is given to Croatia’s contributions to NATO missions and its political and logistical support for Ukraine. These engagements illustrate Croatia’s commitment to NATO’s objectives, including bolstering collective security and deterrence measures against potential threats, notably from Russia. This includes military assistance amounting to €181 million and alignment with EU sanctions against Russia. Despite these efforts, internal political disagreements, such as debates over training Ukrainian forces, reveal Croatia's challenges in balancing national interests with alliance obligations. The research highlights the exacerbation of the "security dilemma" between Croatia and Serbia, driven by differing security policies and the broader geopolitical consequences of the Ukraine conflict. Fueled by the Ukraine conflict, this dilemma is analyzed through the lens of arms races, strategic doctrines, and contrasting geopolitical alignments. The paper suggests that these dynamics aggravate existing mistrust and challenge regional stability in the Balkans. Croatia's NATO-driven deterrence strategy contrasts sharply with Serbia's military neutrality and strategic partnership with Russia, intensifying regional tensions and arms races. These dynamics underline the risk of destabilization in the Balkans if such tensions are not managed through sustained diplomatic efforts. The research offers a critical perspective on how national security strategies interact with multilateral policies, providing new insights into the regional consequences of global strategies like NATO’s deterrence framework. It underscores the need for Croatia and its neighbors to prioritize long-term strategic goals and regional cooperation to mitigate the risks posed by evolving security challenges. The findings emphasize the need for balanced approaches that reconcile national interests with allied obligations to ensure sustainable regional stability.
Keywords: Extended deterrence; Croatia; NATO; Ukraine conflict; security dilemma; regional stability; Euro-Atlantic integration; national security strategies